Changes in the elemental composition of agrocenosis components on gray forest soil under long-term application of mineral and organic fertilizers - A. D. Kotelnikova; T. I. Borisochkina; K. A. Kolchanova; M. A. Shishkin; F. S. Egorov; V. V. Okorkov; O. B. Rogova (Бюллетень Почвенного института им. В.В. Докучаева)
The paper analyzes the elemental composition of soils and plants of agrocenosis on the gray forest soil of Vladimir opolye under long-term application of mineral and organic fertilizers. The content of total and mobile forms of Ni, Cu, Zn, Co, Mn, Fe and the content of these elements in aboveground plant organs, as well as changes in the main agrochemical characteristics that can affect the availability of elements to plants were evaluated. It is shown that the application of mineral fertilizers contributes to soil acidification, increase in the content of organic carbon, mobile forms of phosphorus. At the same time, the variants with joint application of mineral and organic fertilizers are subject to less change of these characteristics, which may be due to the increased buffering capacity of the soil with respect to the components coming with mineral salts, due to the applied organic matter. Introduction of Ni, Cu, Zn, Co, Mn, Fe into agrocenosis with fertilizers (organic and mineral) did not affect the gross content of metals in soil. There was a change in the content of mobile forms of metals in the soil due to changes in agrochemical parameters of soils. Changes in the content of trace elements in plant products were recorded. The reduction of Zn, Cu content in plants on the variants with more intensive use of fertilizers (and with higher yield) is explained by "dilution effect". The low content of Co in the soil and its insufficient supply to the plants must be controlled. The joint use of data on changes in the elemental composition of soils and plants allows better differentiation of experimental variants in the space of principal components when analyzed by this method and is promising for monitoring the consequences of agrogenic load of different degrees. The results obtained can be taken into account in the formation of criteria for assessing the mineral nutrition of plants and fertilizer application rates.